Bimbingan Kelas Ibu Hamil di Kecamatan Mengwi Kabupaten Badung Tahun 2018 - Ni Nyoman Sumiasih; Gusti Ayu Marheni; Ni Wayan Armini; Ni Wayan Suarniti (Poltekkes Kemenkes Denpasar, 2019)
Women class aims to improve the knowledge and skills of mothers through the use of Mother Child Health (MCH) books. But the use of MCH books is not maximal. Service method: group communication with pre-test and post-test. The goal is to increase the knowledge of pregnant women, ready to undergo the process of pregnancy, childbirth, postpartum/ breastfeeding. The activities were carried out at the Kekeran Village Offices of Mengwi District and Mengwi I Community Health Center Meeting Room with a direct demonstration on pregnancy exercise. The target group: 20 pregnant women and health cadres domiciled in Mengwi District. Dedication results: out of 23 class participants of pregnant women, most 74% had secondary education (high school), mostly 20 to 30 years (healthy reproduction) 74%, mostly primigravida 78%. Pre-test results: knowledge of pregnancy, for the most part, was good, about partially good labor. Knowledge of parturition is mostly good. The most knowledge of baby care is good. Partially good family planning knowledge. The yoga gymnastics skills at the time of the pre-test were all participants were exposed. Post test results: knowledge about pregnancy, most (94%) were good. Knowledge of labor is all good. The majority of childbirth knowledge (96%) is good. Most baby care knowledge (91%) is good. Most family planning knowledge is good. After being given gymnastic guidance, all participants can follow it well.Keywords: Guidance, Class of Pregnant Women